Criticism of Government During New Order Era in Film Langitku Rumahku (1989) - Ilma Saakinah Tamsil (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
During the New Order era, all comments, protests against the government, or depicting reality would receive harsh punishment, and some would be arrested. The government silences everyone’s right to freedom of speech and express opinions through state security measures. The film Langitku Rumahku (1989) owned by Slamet Rahardjo and Erros Djarot had become a controversial film because it dared to describe a picture of social differences between two classes of society which was interpreted as a criticism of the New Order government at that time so finally this film had its broadcast period limited and withdrawn from circulation. This study aims and focuses on describing criticism of the New Order government in the film Langitku Rumahku. To approach this problem, the Semiotics theory (Ferdinand de Saussure) is used to see signifier and signified which is strengthened by several social theories to describe the socio-political atmosphere of that era. Data were collected through films and analyzed qualitatively. This study concludes that criticism is clearly illustrated through the discrimination of the characters, symbols, and dialogues displayed in the film so that they have relevance to the research objectives.